GLOMERULAR HYPERFILTRATION MAY CONTRIBUTE TO RENAL TROPISM AND KIDNEY INJURY IN COVID-19 BY UPREGULATING ACE2 IN HUMAN PODOCYTES. (June 2022) - Bolbrinker, Juliane; Mangelsen, Eva; Kourpa, Aikaterini; Debora, Kaiser; Daniela, Panakova; Reinhold, Kreutz
Abstract : Objective: Apart from the respiratory system, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can potentially infect multiple other organs including podocytes in the kidney. The latter play a crucial role in glomerular filtration. Podocytes can be damaged by increased fluid flow shear stress (FFSS) of the ultrafiltrate in Bowman's space in the setting of glomerular hyperfiltration that occurs in disease states such as hypertension, diabetes or in several forms of chronic kidney disease. These conditions are associated with an increased risk of a more severe course of coronavirus disease 2019 (COVID-19) and mortality. Design and method: To assess the susceptibility of human podocytes (hPC) for SARS-CoV-2 infection in the context of hyperfiltration in vitro, we used a recently established model system (Streamer® Shear Stress Device)) to mimic hyperfiltration by exposing hPC to increased FFSS of 1 dyne/cm 2 for 2 h. In this setting we nalysed the effects of FFSS on mRNA expression of angiotensin I-converting enzyme 2 (ACE2) as the pivotal entry receptor for SARS-CoV-2 infection in hPC. Moreover, other potential critical host cell factors including transmembrane serine protease 2 (TMPRSS2), furin (FURIN), and neuropilin 1 (NRP1) were also assessed in parallel with changes of the F-actin fiber structure, i.e. an important cytoskeletal marker in hPC. Results: Under control conditions, hPC displayed long, parallel F-actin fibers crossing the entire cell body. After FFSS, an enrichment of cells that express F-actin in a cortically condensed pattern near the cell membrane was observed. FFSS induced a significant upregulation of ACE2 expression (about twofold) and of all other nalysed SARS-CoV-2 entry factors in hPC (p < 0.05, respectively compared to control conditions, Figure 1 with data plotted as log2fold change [FC]). Conclusions: Our data support a potential link between glomerular hyperfiltration, podocyte damage and renal tropism of SARS-CoV-2 that may contribute to kidney damage including albuminuria development in COVID-19 patients.